ISSUES IN INCLUSION AND INDIVIDUAL LEARNING NEEDS LEARNING TO READ. (August 2016) - McMurray, Sharon; Thompson, Ross
Abstract : For many lower ability children, inclusion in the mainstream setting does not guarantee that that their individual needs will be met. With increased numbers of children with well‐below average ability being placed in mainstream schools, it is imperative that teachers understand factors which impact on learning for this group of children. Current trends in the teaching of reading may present barriers to learning for children who have moderate learning difficulties and severe literacy difficulties.